1991
DOI: 10.1016/0091-3057(91)90588-s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective opiate antagonists on morphine-induced hyperalgesia in domestic fowl

Abstract: Sufka, Kenneth Joseph, "Effects of selective opiate antagonists on morphine-induced hyperalgesia in domestic fowl " (1990 INFORMATION TO USERSThe most advanced technology has been used to photograph and reproduce this manuscript from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This is consistent with clinical observations that OIH is an increase in nociceptive sensations whereas other senses are unchanged [32; 88]. Opiate receptors, especially the mu-opiate receptor (MOR), are critically involved in OIH [17; 66; 86] and MOR-deficient mice are not hyperalgesic after opiate treatment [46]. We suggest that MORs on small diameter DRG neurons are instrumental in initiating OIH.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with clinical observations that OIH is an increase in nociceptive sensations whereas other senses are unchanged [32; 88]. Opiate receptors, especially the mu-opiate receptor (MOR), are critically involved in OIH [17; 66; 86] and MOR-deficient mice are not hyperalgesic after opiate treatment [46]. We suggest that MORs on small diameter DRG neurons are instrumental in initiating OIH.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Tilson et al [ 4 ] first demonstrated that abrupt cessation of opioids induced decreased pain thresholds in rats and showed that this enhanced pain sensitivity was highly correlated with the administered dose of opioid. Other animal studies followed, [ 2 , 5 , 6 , 7 ] all supporting the occurrence of OIH. Consistent with these animal results, clinical investigators demonstrated the occurrence of OIH after intraoperative remifentanil infusion, characterized by increased pain, combined with increased consumption of postoperative opioid, which in turn, resulted in decreased opioid efficacy [ 8 ].…”
Section: Evidencementioning
confidence: 84%
“…MOR could form a molecular complex with TRPM8 to enable the activation of PLD, similarly to other G protein-coupled receptors (GPCRs), 15, 32, 72 as was recently shown for 5HT1b and TRPM8. 89 MOR is critical to OIH 82 and presumed to be also key to morphine induced cold hyperalgesia. MOR and TRPM8 are mainly expressed in small sized DRG neurons.…”
Section: Discussionmentioning
confidence: 99%